Literature Review of Domestic Randomized Controlled Trials for Hominis Placenta Pharmacopuncture - Hea Sun Chun (MEDrang Inc., 2024)
This study was conducted to analyze research trends, quality, and bias of pharmacopuncture studies, etc., on domestic randomized controlled trials (RCTs) using hominis placenta pharmacopuncture (HPP). A total of 13 domestic RCTs were selected by searching two domestic online databases (Research Information Sharing Service and Oriental Medicine Advanced Searching Integrated System). The publication of domestic RCTs using HPP began in 2000, and most studies targeted peripheral facial paralysis and gynecological diseases. Most studies have shown the Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) checklist reporting rate of > 50.0%; however, four subitems, including "depth of insertion," showed a reporting rate < 50.0%. Some studies have shown significant improvement in the HPP group; however, the sample size was diverse, the observation period was short, the effect of stimulation of the same acupoint between the two groups could not be ruled out, and the overall risk of bias was mostly "some concern." In addition, further development of STRICTA that reflects the characteristics of pharmacopuncture therapy is necessary.